Study of Aptamer-Attached Juglone in Different pH Ranges and Ionic Concentrations of Buffers: Electrochemical aptamer-based sensors - Mehdi Saberian; Davoud Asgari; Yadollah Omidi; Hossein Hamzeiy (Iranian Journal of Pharmaceutical Sciences, 2012)
Electrochemical aptamer-based sensors attract a lot of interest as useful methods because of their low cost, accuracy, sensitivity, and simplicity. An electro-active redox molecule comprises the main part of the electrochemical-based sensors. Ferrocene is one of the most popular redox molecule used in biosensor fabrication. But, instability of ferrocenium ion in strong nucleophilic reagents and chloride containing solutions is one of the main problems of this redox molecule. In this study, Juglone is used as an effective quinone redox molecule for aptasensor designing in different pH ranges and different concentrations of chloride ion. The voltammetric studies showed that the electrochemical response of sensor increased by raising the buffer ionic concentration and the sensor accuracy in 7.0 to 8.0 pH range as well. According to the findings, Juglone could be used as an effective redox molecule in high concentrations of chloride containing solutions in the 7.0 pH.